Pengembangan Handout Berbasis Kontekstual Disertai Peta Konsep Pada Materi Bahan Kimia Dalam Kehidupan Untuk Siswa SMP - Muharti, Sisri; Fifendy, Mades; Susanti, Diana (Pendidikan Biologi, 2014)
Handout is written material that prepared by teacher for students. The teacher can make handout by some literatures that have relevance from basic competence that will be achieve by students. Based on researcher observation and interview with teacher who teaches biology at SMPN 2 Lembah Gumanti, learning process had used handout but it is still not interested because there is only theory without contextual picture and also not enough sources. Then, based on interview to students, the researcher found that not all of students have handout. Next, the aim of this research is to produce a handout that contextual principle and have mapping on chemicals material in life that valid and practice. The type of this research is development research by procedural model that have a purpose to produce a product. The product will be developed by three steps of four D Models. They are defined, designed, and developed. The first step (define) is consist of curriculum analysis and students analysis. The second step (design) is done handout designed that contextual principle by using mapping on chemical material in life for junior high school students. Then, the third step (developed) is done validity test by two lecturers and two teachers at SMPN 2 Lembah Gumanti. Then, practicalities test by two teachers and twenty two students of SMPN 2 Lembah Gumanti. The data analyzed by using presentence technique and descriptively. The result of validity test is indicated that the handout is valid by criterion 88,8% viewed by didactic aspect, construction, and technique. Then, the result of practicalities handout test by teacher is very practice with criterion 90,8% meanwhile practicalities handout test by students with criterion 85,9%. In conclusion, the researcher found that handout made by teacher is valid and practice.